Improvements on aircraft engine emission and emission inventory asesessment inside the airport area. (1st December 2017) - Zaporozhets, Oleksandr; Synylo, Kateryna
Abstract: The effects of aircraft engine emissions within the planetary boundary layer under the landing/take-off operations contribute sufficiently to deterioration of air pollution in the vicinity of the airport and nearby residential areas. The aircraft emission inventory is usually calculated on the basis of certificated engine emission indices, which are provided by the engine manufacturers and reported in ICAO engine emission database. The emission indices rely on well-defined measurement procedure and conditions during aircraft engine certification. Under real circumstances, however, these conditions may vary and deviations from the certificated emission indices may occur due to impact such factors, as: the life expectancy (age) of an aircraft; the type of an engine installed on an aircraft; meteorological conditions. Analysis of emission measurement data for aircraft engine concluded that method, which takes into account the influence of the real operational (fuel flow rate, operation period of engine/age and its maintenance) and ambient temperature on emission indices, allows to get more precisely the results of emission inventory of the aircraft, their contribution to total inventory and local air quality analysis in airports.